2004
DOI: 10.1081/pfc-120027436
|View full text |Cite
|
Sign up to set email alerts
|

Pyrethrins and Piperonyl Butoxide Adsorption to Soil Organic Matter

Abstract: The adsorption and mobility of pyrethrins (Pys), the major insecticidal components obtained from the pyrethrum daisy Tanacetum cinerariifolium, and piperonyl butoxide (PBO), a pyrethrum synergist, were determined in soil using batch-equilibrium and reverse-phase thin-layer chromatographic techniques. Two soil management practices were used, soil mixed with yard waste compost (COM) at 50 t acre(-1) on dry weight basis and no-mulch (NM) bare soil. Adsorption isotherm experiments were carried out using known conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 18 publications
2
10
1
Order By: Relevance
“…For hydrophobic compounds, having the least soluble compound or the highest K OW will adsorb most strongly on soils (Oudou and Hansen 2002a). Similar results were obtained by Antonious et al (2004), who indicated that the two most important characteristics determining soil adsorption towards pesticides were the organic matter content of the soil and the water solubility of the organic compound. Chiou et al (1979) also found that adsorption of non-ionic compounds on soil particles depended directly on the organic carbon content (K OC ) of the adsorbing phase.…”
Section: Discussionsupporting
confidence: 89%
“…For hydrophobic compounds, having the least soluble compound or the highest K OW will adsorb most strongly on soils (Oudou and Hansen 2002a). Similar results were obtained by Antonious et al (2004), who indicated that the two most important characteristics determining soil adsorption towards pesticides were the organic matter content of the soil and the water solubility of the organic compound. Chiou et al (1979) also found that adsorption of non-ionic compounds on soil particles depended directly on the organic carbon content (K OC ) of the adsorbing phase.…”
Section: Discussionsupporting
confidence: 89%
“…The greater the K OC value of a pesticide, the stronger the binding to the soil. [24][25][26] Walker and Welch [27] studied the degradation rates of three herbicides and their strengths to adsorption; their results showed an order of degradation rate of metribuzin > alachlor > atrazin and an order of adsorption of alachlor > atrazin > metribuzin. Metribuzin mineralization to 14 CO 2 proceeded more slowly in amended soil than in unamended soil.…”
Section: Resultsmentioning
confidence: 98%
“…The greater the K OC value of a pesticide, the stronger the binding to the soil. [17,18] Dimethazone is highly soluble in water (1100 mg L −1 ) and has a Koc of 150-562 mL g −1. [19] These properties indicate its potential mobility and aquatic environmental pollution.…”
Section: Resultsmentioning
confidence: 99%